(3JhVjM GdJPcQI ` aj Yde GdgjFIs - (3GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQqi, fXGe GdOjf, hjbGd dg GdCYQL ` HYO (B850 (3g` s; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s
(3ChdgG (B:s
(3hHYO , jbhd (B: (3ef GdeYdhe Cf GdYdhe JJHGjf ai GdTQa HMSH JHGjf ehVhYGJgG hgh Yde gjFI GdCadGc hCf cJGH GdJPcQI ai gPG Gdaf GdefShH Edi GdWhSi Cf CcJH ajg TQMkG jPdd ef GddaX UhGHg s
(3BNQgG (B:s
(3aEf GdCYeGd HGdfjGJ , hHgG JLdH GdHQcGJ , hJfGd GdOQLGJ hGdMeO deHOY Gdcd hbO EJab aQGZi ef JCdja gPG GdcJGH s
(3CJe GdeDda JCdjag SfI (B711(3g`s
(3HBNQgG bQGAI eMeO Hf geGe GdTjQGRi HNWg Ydi GdeDda eQGQkG eDQNI ai QeVGf (B719(3g` HgG fXGe GdJYbjHIs
(3HgG CTcGd hQShes
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdadcs